On the Counterpoint of Rhythm and Meter: Poetics of Dislocation and Anomalous Versification in Parmenides’ Poem - Berruecos Frank, Bernardo (Revista Archai, 2024)
In ancient times, authors such as Plutarch and Proclus questioned Parmenides’ abilities as a poet considering his Poem to be ‘prose in disguise’. Harsh judgments concerning Parmenides’ style are pervasive even in modern scholarship (Diels, <a href="https://www.scielo.br/j/archai/a/SxsyXLHx8wmRjz6Xwvy8c3h/?lang=en#B8_ref" data-ref="DIELS, H. (1897). Parmenides Lehrgedicht. Berlin: Druck und Verlag Georg Reimer. (2nd ed. with a new preface by Walter Burkert and a revised bibliography by Daniela De Cecco. Sankt Augustin: Academia Verlag, 2003).">1897; Wilamowitz, 1912; Tarán, <a href="https://www.scielo.br/j/archai/a/SxsyXLHx8wmRjz6Xwvy8c3h/?lang=en#B36_ref" data-ref="TARÁN, L. (1977). Concerning a New Interpretation of Parmenides. Gnomon, v. 49, p. 651-666. (Review-Article of A. P. D. Mourelatos, The Route of Parmenides) = in (2001) ">1977; Kirk & Raven, <a href="https://www.scielo.br/j/archai/a/SxsyXLHx8wmRjz6Xwvy8c3h/?lang=en#B23_ref" data-ref="KIRK, G. S.; RAVEN, J. E. (1977). The Presocratic Philosophers. A Critical History with a Selection of Texts. Cambridge: Cambridge University Press. ">1977). This paper focuses on specific metrical and rhythmic devices used consistently in the composition of the Poem, that I will refer to, collectively, as ‘poetic dislocation’. This term encompasses the blurring and cancellation of the central caesura, the tendency to break Hermann’s bridge with varying degrees of intensity, the accumulation of enjambment in groups of verses, the use of non-traditional lexicon of the epic genre and the placement of Homeric lexicon in non-Homeric hexameter collocations. My attempt is to prove that these procedures are an integral part of Parmenides’ poetic style. I will also present an analysis of Parmenides’ versification focusing on the rhythmic patterns and the organization of caesura, especially in fr. B8.